Walter the farting dog goes on a cruise - Kotzwinkle, William (Dutton Children's Books, 2006)
Because his farts create unpleasantness for everyone on a cruise ship, Walter the dog continues the journey in a lifeboat, but when the ship's computer crashes, causing the liner to drift, Walter again proves himself a hero.